Avaliação da Aprendizagem na Licenciatura em Matemática a Distância - Costa, Priscila Kabbaz Alves da (2013)
This study presents an analysis of the learning evaluation process developed in the Distance Teaching Mathematics curse, offered by the Ponta Grossa State University (UEPG), in partnership with the Brazil Open University (UAB). The qualitative nature of this multiple case study, aimed to analyze the learning evaluation process developed in subjects taught in the course and was developed from the following problem: how does the learning evaluation developed at the Distance Mathematics teaching Course – EaD can contribute to the initial instruction of teachers? The characterization of the historical background of EaD in the world and in the Brazilian context, the constitution of such model of distance teaching in UEPG and the partnership UEPG/MEC/UAB to offer graduation courses, mainly Mathematics teaching were discussed in the first chapter. The theoretical background of this study regarding educational, learning and distance learning evaluation was built on the contributions of Hadji (2001), Fernandes (2009), Brandalise (2010), Dias Sobrinho (2003), Cappelleti (2010), Kenski (2010), Valadares (2011), Sousa (1991), Silva (2010), Silva (2011), Behar and Notare (2009), Álvarez Méndez (2002) and Luckesi (2011), Okada( 2003,2006) amongst others. The methodological approach was based on Flick (2007), André (2005), Oliveira (2007) and Lüdke (1998). In order to study multiple cases, the procedure chosen was the analysis of documents as follows: The Course Pedagogical project (CPP), printed teaching material, the learning virtual environment (LVE) of the subjects selected: Instrumentation to the teaching of Mathematics II, Geometry II, Fundaments of Mathematics II and Introduction to Integral Differential calculus, together with evaluation activities, forums, tasks, questionnaires, course book and tests. The research results revealed that although the EaD teaching model has particularities in the evaluation process, the epistemological and methodological fundaments of learning evaluation are relevant for both the attendance and the distance teaching. The learning evaluation analyses showed that the implementation of a diagnostic, formative and student centered process evaluation, as proposed by the course CPP is still incipient and a great challenge for all individuals involved in the evaluation process - teachers, tutors and students – once the author/instructor teacher‟s conception of teaching and learning is usually what defines the students‟ instruction trajectory, together with the LVE organization in order to enable the construction of the mathematics knowledge by the student, and the choice of evaluation instruments. As the summative perspective with a rationalist and traditional base of learning evaluation still prevails, towards the results obtained by the students rather than the learning process, the number of drop outs and failure are significant. The weaknesses of learning evaluation processes, however, should be discussed and improved by their practitioners considering that there is a relevant social value in the offer of distance learning courses which represents the possibility of qualifying professionals to work with mathematics teaching in places where there are no higher education institutions.